Imbalanced Development Challenges of China from 1990 to 2015 - Shahriari, Shohreh; Shirzadi, Reza (Journal of History Culture and Art Research, 2017)
China’s economic development surprised the political and economic experts since the last four decades. China obtained a desirable economic development in the world. It also enhanced its position in the international system as a global power. In the late 1970s china’s outstanding growth took place following the political development as well as elites’ movement. The advent of pragmatism and development oriented thought replaced with the ideology-oriented thoughts in this decade. Despite the outstanding achievement in the economic field, China couldn’t strike a balance between politics and economic field as well as its development. Today it has been proven that the industry- economic development is impressive just by cultural- political enhancement, so in this way, it is possible to minimize the advent of crisis and failure. The purpose of the current study is investigating the main challenges toward the one-dimensional development in China.